Hidroxiapatita como sistema para liberação de ibuprofeno - Pereira, Mariana de Brito Batista (2014)
Hydroxyapatite has been explored as an excellent biomaterial due its compatibility with the bone tissue, mainly with application to the drug adsorption. This work aimed to synthesize hydroxyapatite with controlled porosity, through co precipitation method using casein as template and to investigate the loading capacity of the ibuprofen in the obtained hydroxyapatite. Therefore in this study, it was synthesized hydroxyapatites with the calcium nitrate, calcium chlorite e ammonium phosphate. The solids were characterized by X ray diffratometry, N2 adsorption/dessorption measurements, infrared spectroscopy, thermogravimetry and scanning electron microscopy. The synthesis reproducibility was verified. The solid was used to carry and to deliver ibuprofen drug. The synthetized matrices, with and without template, formed monophasic compounds, which were indexed to hydroxyapatite. Surface area values were 114 e 147 m2 g-1 for the solids obtained with calcium chlorite and calcium nitrate, respectively. The loading study indicated higher drug incorporation when the solvent polarity decreased at 24 h and room temperature. For the adsorption tests, the maximum loading values were 188 and 184 mg g-1 in ethanol and hexane, respectively at reaction times of 120 and 360 min. The release tests showed a fast kinetic at the first 24 h, and more slower process after this time. The equilibrium time was reached after 38 h with a maximum release about 97% for the ibuprofen on mesoporous solid